Judo Economics in Markets with Multiple Firms. (13th November 2014) - Cracau, Daniel; Franz, Benjamin
Abstract : We study a sequential Bertrand game with one dominant market incumbent and multiple small entrants selling homogeneous products. Whilst the equilibrium for the case of a single entrant is well known from Gelman and Salop (1983), we derive properties of theN -firm equilibrium and present an algorithm that can be used to calculate this equilibrium. The algorithm is based on a recursive manipulation of polynomials that derive the optimisation problem that each of the market entrants is facing. Using this algorithm we derive the exact equilibrium for the cases of two and three small entrants. For more than three entrants only approximate results are possible. We use numerical results to gain further understanding of the equilibrium for an increasing number of firms and in particular for the case whereN diverges to infinity. Similarly to the two-firm Judo equilibrium, we see that a capacity limitation for the small firms is necessary to achieve positive profits.